REPORTING GUIDELINES AND CHECKLISTS TO IMPROVE MEDICAL WRITING - Badar, Ahmed (Pakistan Journal of Physiology, 2013)
Pobody’s nerfect. All of us sincerely work hard to make our research, articles and journals perfect, however no author, reviewer or editor can ever be ‘know all’ or ‘do all correct’. Quality control has been the main theme for all services over the last quarter of a century. The medical journalism was never an exception. The last two decades were especially important in the history of medical journalism as measures for quality control were developed, tested, standardised and applied. The products of these extraordinary efforts are various guidelines, checklists and flow diagrams that are now part and parcel of modern medical journalism. These tools make the task of authors, reviewers, and editors easy. They provide a systematic way by which authors know exactly how a particular manuscript is to be prepared, the reviewers make out what they are supposed to evaluate and the editors identify problems with submitted as well as reviewed or corrected manuscripts. Another valuable and highly recommended use of these materials is critical appraisal of published articles (journal clubs). Identifying the relevant reporting guidelines, checklists and flow diagrams and following them in letter and spirit can ensure hassle free publication of our manuscripts, as all quality journals have (or are) implementing them.